Containing Muslim extremism and radicalism - Wan Mohd Nor Wan Daud (Universiti Kebangsaan Malaysia, 2010)
This article argues that wars, atrocities, radicalism and extremism have been caused by many interrelated external socio-economic, political and ethnic factors, even though religious communities are involved. However, internal factors such as the role of religious education, are instrumental in understanding religious radicalism and extremism, including among some Muslims. This article also elucidates the dual nature of Islamic religiosity in Asia i.e. its manifested diversity and underlying unity, traces Muslim historical treatment of religious extremism, and suggests that certain methodological and doctrinal aspects of contemporary Islamic education may have contributed to an extremist outlook and behavior. It offers a few specific and practical recommendations involving the external and internal factors to significantly reduce the phenomena of extremism among Muslims, especially in Asia